Segregação ocupacional por gênero e raça: uma análise para o Brasil e o Maranhão nos anos 2012 e 2022 - SILVA, Patrícia Natália Santos (2024)
Despite social advances in recent decades aimed at reducing gender and racial inequalities in Brazil, women and Black individuals still face significant and persistent disadvantages, especially in the labor market. Discrimination and occupational segregation are determining factors in these observed inequalities. Most existing studies analyze disparities between gender or racial groups, but there is a shortage of analyses that investigate these dynamics in an integrated manner. This dissertation sought to understand how the intersection of gender and race influences workers' behavior and income disparity. Microdata from IBGE's Continuous PNAD were used, classifying occupations as racially integrated or segregated. This classification helped identify occupations predominantly held by Whites, Blacks, and those racially integrated, for both men and women. In addition to national analysis, the study specifically focused on the state of Maranhão due to its distinct racial composition compared to Brazil, recognizing the importance of analyzing local labor markets due to regional heterogeneity in the country. The results contributed to a deeper understanding of inequality dynamics in the Brazilian labor market, providing insights for public policies aimed at reducing gender and racial disparities.